1983
DOI: 10.1029/rs018i006p00895
|View full text |Cite
|
Sign up to set email alerts
|

Solar cycle and seasonal variations of the ionosphere observed with the Chatanika incoherent scatter radar

Abstract: An incoherent‐scatter radar facility was operated at Chatanika, Alaska (geographic and invariant latitudes both ≈ 65°N) for almost 11 years, essentially a full solar cycle. During this period, experiments lasting 24 hours and directed at nearly overhead measurements were made approximately once per month. The seasonal and solar cycle dependences of the ionosphere over Chatanika as deduced from 108 experiments spanning the 11 years are presented. The basic parameters measured were electron concentration, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 5 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…However, on the basis of the Chatanika incoherent radar observations, Baron et al. [6] found that anomalies also exist in Alaska (65.1 • N). The winter anomaly at Tromsoe (69.6 • N, 19.2 • E) was reported by Farmer et al [7] .…”
Section: Introductionmentioning
confidence: 99%
“…However, on the basis of the Chatanika incoherent radar observations, Baron et al. [6] found that anomalies also exist in Alaska (65.1 • N). The winter anomaly at Tromsoe (69.6 • N, 19.2 • E) was reported by Farmer et al [7] .…”
Section: Introductionmentioning
confidence: 99%
“…It therefore also appears inconsistent that the ionization enhancement is due to local cusp related soft particle flux. This of course assumes that the spatial extent of the cusp does not Baron et al [1983] for summer is 2.6 x 105cm -3 and the measured value was 3.0 x 105cm -3. The variation in the peak densities on the two days is also consistent with the known seasonal variations of the O-to-N 2 ratio (i.e., the winter anomaly) as discussed by Roble [1977].…”
Section: Introductionmentioning
confidence: 99%
“…Baron and Wand (1983a), however, reported these anomalies in Alaska (65.1 • N) on the basis of the Chatanika incoherent radar observations. A couple of years later, the winter anomaly at Tromsφ (69.6 • N, 19.2 • E) was reported by Farmer et al (1990).…”
Section: Introductionmentioning
confidence: 99%